1977
DOI: 10.1007/bf02781340
|View full text |Cite
|
Sign up to set email alerts
|

Clinical studies on dissolution of gallstones using ursodeoxycholic acid

Abstract: Ursodeoxycholic acid (UDCA), 7beta hydroxy epimer of chenodeoxycholic acid (CDCA), has been used as a choleretica for 20 years in Japan. Recent report showing increased excretion of UDCA in bile after CDCA administration may suggest the possibility that UDCA has similar effects to CDCA on bile cholesterol unsaturation and on gallstone dissolution. The present paper describes the clinical usefulness of UDCA for gallstone patients during the past two years. Seventy-four gallstone patients with functioning gall-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Our overall success rate of 19% of patients achieving complete dissolu tion, or 25% of those treated for at least 6 months, is comparable with other studies [2,3,9,13,20,22], using various doses of UDCA, usually for only 6-12 months. Equal efficacy for the lower dose was confirmed in the separate analysis of stones less than 10 mm in diameter, which fact is important as our results confirm previous findings that stone size is a significant predictor of re sponse to UDCA [13,22], Interpretation of other published dose comparison studies of UDCA evaluating gall-stone dissolution rather than biliary lipid changes is not easy as several such studies are of small numbers of patients, or follow-up has been limited, with extensive use of partial dissolution as an end-point.…”
Section: Discussionsupporting
confidence: 76%
“…Our overall success rate of 19% of patients achieving complete dissolu tion, or 25% of those treated for at least 6 months, is comparable with other studies [2,3,9,13,20,22], using various doses of UDCA, usually for only 6-12 months. Equal efficacy for the lower dose was confirmed in the separate analysis of stones less than 10 mm in diameter, which fact is important as our results confirm previous findings that stone size is a significant predictor of re sponse to UDCA [13,22], Interpretation of other published dose comparison studies of UDCA evaluating gall-stone dissolution rather than biliary lipid changes is not easy as several such studies are of small numbers of patients, or follow-up has been limited, with extensive use of partial dissolution as an end-point.…”
Section: Discussionsupporting
confidence: 76%
“…Simi lar results have more recently been reported with ursodeoxycholic acid (UDCA) [3,4]. This drug seems to be active even if adminis tered for a shorter time or in smaller doses than CDCA [5][6][7], This paper reports the results of a multi center study carried out on 116 patients in some Lombard hospitals on the litholytic ac tivity of CDCA and of two different doses of UDCA.…”
mentioning
confidence: 54%
“…Al though gallstone size is believed to be impor tant by some groups using either CDCA therapy (14,21) or UDCA (19,20), others have not found size to be of much (23) or indeed any (4) importance in determining outcome. There is no reason why larger stones should be resistant to dissolution therapy although, of course, a complete response may reasonably be expected to take longer.…”
Section: Discussionmentioning
confidence: 99%
“…Chenodeoxycholic acid (CDCA) has been shown to dissolve gallstones most effectively with large doses (15 mg/kg body weight, or 1,000 mg/day) (2, 4. 10, 14, 23); but it has been suggested that UDCA may be more potent (19,20) and relatively smaller doses might be optimal. An analysis of the biliary lipids indicated that UDCA treatment reduced biliary cholesterol in gallstone disease (5,16,17,19,22) although cholesterol satura tion was reduced inconsistently by lower doses (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation